Comparative statistical evaluation of greenness, blueness, and whiteness spectrophotometric methods for dexamethasone and chloramphenicol estimation - Heidi R. Abd El-Hadi (Scientific Reports)
Abstract Five sustainable and validated UV spectrophotometric methods were developed for analyzing chloramphenicol (CHL) and dexamethasone sodium phosphate (DSP) in pure and ophthalmic dosage forms. CHL was detected by zero order spectra method at 292.0 nm in the range 2.00–32.00 µg/mL with limits of detection (LOD) and quantification (LOQ) of 0.96 and 2.88, respectively. DSP was analyzed using the following four techniques: Induce dual wavelength (IDW), fourier self-deconvolution (FSD), ratio difference (RD), and derivative ratio (DD1). The IDW method used at 239.0 and 254.0 nm with a linearity range of 4.00–40.00 µg/mL with LOD and LOQ values were 0.93 and 2.79, respectively. The FSD approach used at 242.0 nm, with a linearity range of 2.00–32.00 µg/mL and 0.65, 1.95 as values of LOD and LOQ, respectively. In the linearity range of 4.00–32.00 µg/mL, RD and DD1 are applied. RD is utilized at 225.0–240.0 nm, while DD1 is carried out at 249.0 nm. Values of LOD and LOQ for RD were 0.70 and 2.10 while for DD1 were 0.80 and 2.40, respectively. These methods were evaluated for their environmental sustainability and validated according to ICH guidelines, overcoming challenges like spectral overlap and collinearity. Statistical comparisons with published methods revealed no significant differences.